MEDIATING LANGUAGE AND CONTENT: TEACHER-STUDENT INTERACTION IN A CLIL PRIMARY MATH CLASSROOM - Sihombing, Eltri Anggi Goklas Pinarsita; Nurjanah, Faiz; Rahmah, Siti Jakiah; Huwaida, Faizah; Syifa, Farahiyah Marwa; Fitria, Risa (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study investigates how teacher-student interaction influences student engagement, understanding, and language development in a bilingual CLIL mathematics classroom. The study aimed to examine how such interactions support learning in both content and language. This research was conducted using a qualitative method involving two classroom observations and one semi-structured interview with a fourth-grade teacher at SD Presiden. The findings revealed that the teacher applied a student-centered approach through strategies such as open-ended questions, real-life examples, and consistent bilingual scaffolding. These methods significantly enhanced student engagement and gradually developed their English language proficiency within the context of mathematics learning. Although Indonesian remained the dominant language of student expression, the increasing use of English for key mathematical terms indicated positive language exposure. The study concludes that teacher-student interaction in a bilingual CLIL classroom plays an essential role in supporting dual development—mathematical understanding and English language acquisition—by creating an interactive, supportive, and linguistically rich learning environment.